KONFLIK PSIKOLOGIS TOKOH NOVEL KAU, AKU, DAN SEPUCUK ANGPAO MERAH KARYA TERE LIYE (KAJIAN PSIKOLOGI SASTRA) - Nunuk Nuriyati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The aims of the reseach are to describe the worry of characters, the fear of characters, the disappointment of characters, the anxiety of characters, and the doubt of characters in “ Kau, Aku, dan Sepucuk Angpao Merah” novel by Tere Liye. This study was a descriptive qualitative research with content analysis method. Data were collected by researcher where data was recorded and analyzed during periode of research to collect data from novel’s text, then it processed and further analyzed in detailed. The results of the researh are the psychical conflict of characters in “ Kau, Aku, dan Sepucuk Angpao Merah” novel by Tere Liye as follow (1) the characters have worries of condition, characters have fear of lossing the close freind, fear of the reality, and fear of hurting the feeling (3) the characters have disappointment for job, the close freind that left them, getting something that’s wanted, (4) the caracters have anxiety beacause their freinds are kept at a distance from them, and (5) the caracthers have the doubt for choosing the job, deciding a choice, and doubt for the condition.